Sistem Informasi Pelayanan Jasa Laundry Sepatu Pada Queen Shoes Cleaning - Syifa Nur Rakhmah; Irfan Rizki (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The development of information technology at this time plays an important role in helping problems in the process of an activity, one of which is in the field of business or business at the Queen Shoes Cleaning store. The process used at this time still uses manual methods such as recording services, making reports, and also storing transaction evidence that is still messy, of course, there is a very big risk of losing the documents in the store. For this reason, the author makes the idea of ​​building a website-based information system in which you can order services, print reports, make receipts, and see shoe washing prices. There are 3 users in this system, namely regular visitors, registered visitors, and admins. For ordinary employees can only see the price list, about the store, the type of service. Then members can make transactions, print transaction receipts, and admins can process incoming transactions, print incoming reports, view user data, and view admin data. Keywords: Analytical Hierarchy process, Laundry Shoes, Codeigniter, Laravel.